Post-Election Economic and Business Challenges: Leadership Transition from President Susilo Bambang Yudhoyono to President Joko Widodo in Indonesia - Pratama, Evander Dio; Rahma Diva Anjani; Ngatihat, Gheyza Fiyolent Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Post-election economic and business challenges are the main focus in facing the leadership transition from President Susilo Bambang Yudhoyono to President Joko Widodo in Indonesia. This research investigates the economic and business challenges following political elections on economic stability and business conditions in Indonesia. A thorough analysis was conducted to evaluate the economic policies implemented by both governments and their impact on economic growth, investment and the overall business climate. By considering the challenges and opportunities faced, this research also identifies strategies that can be taken to strengthen the Indonesian economy and business in the context of a dynamic leadership transition. The research method used in this study is a literature review. This approach involves comprehensive collection and analysis of relevant literature, articles, research reports and publications related to the theme discussed.